KOMET-QR Kartu Eksplorasi Etnomatematika-QR Pada Materi Bangun Datar Kelas IV Sekolah Dasar - Solihin, Annas; Rahmawati, Ika (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2024)
KOMET-QR (Quick Response Ethnomathematics Exploration Card) is an innovative learning media that combines Ethnomathematics and QR-Code technology, providing an interactive experience between digital resources not only in the classroom, but also facilitating learning outside class hours. With interactivity, contextuality, and respect for local wisdom, KOMET-QR is effective in increasing understanding of Bangun Datar for fourth grade elementary school. This research is development research or Research and Development (R&D) using the ADDIE development model. The research results showed material validity of 94% and media validity of 97.33%, both in the "Very Valid" category. Media effectiveness was 98.31%, with the category "Very Effective," seen from a significant increase in the posttest. Practicality reached 96.95% with the category "Very Practical." With high validity, effectiveness and practicality results, KOMET-QR was declared suitable for use in learning activities.